Karo Traditional Oil, a traditional herbal medicine from Indonesia promote wound healing acceleration by suppressing tumor necrosis factor – α and stimulating interleukin 10 production - Primadina, Nova (Gaceta Médica de Caracas, 2021)
Introduction: Wound healing acceleration is often found on open wounds smeared with Karo Traditional Oil, but its mechanism of action is unknown. Therefore, this study aimed to assess the mechanism of action of active compounds in Karo Traditional Oil in the inflammation phase of the wound healing process.